Enterprises' internationalisation strategy: skills in exportation and customs law - Ribeiro, Maria Clara Dias Pinto (2013)
Economical development has always been connected to the commercial exchanges between people, due to the necessity to suppress their needs. With the increasing growth of international business and more competitive and demanding markets, exportation has become an important first step to internationalisation. Unlike what happened in the past, companies must be aware that the enrolment in the current global market is risky and requires elaborated technical procedures. Internationalisation should not be treated as an isolated event of business management. The first part of this paper aims to understand the export process and fit it in the current stage of international trade, keeping in mind the framework of export under the customs law. Then, we tried to understand how Portuguese companies should face this process in their internationalisation strategy, and what skills organisations must acquire to be able to export competitively in the current scenario of globalisation. The investigation was based on interviews in companies that, through a process of internationalisation by exportation, have implemented themselves strongly in extern markets. This investigation allowed us to analyse the companies’ motivations to become international, as well as the selection criteria for the export destinations. It was also possible to identify the main obstacles to the internationalisation of Portuguese companies. We concluded that companies that choose exportation as a way to become international acquire specific skills that enable them to become competitive in international trade. However, studies have failed to answer the second initial question about whether the measures implemented by Customs potentiate exports.